Implementation of Marketing Communication Strategy in Building Brand Awareness Talkshow Program - Galih Ginanjar Saputra; Edwin Perdana Adiwijaya; Fadhilah Fadhilah; Nanda Salsa Kamelia (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The development of digital media has changed people's information consumption patterns, thus requiring conventional media to adapt marketing communication strategies. This study aims to analyze the implementation of Metro TV's marketing communication strategy in increasing brand awareness of Q&A talk show programs. Data were collected through in-depth interviews, observations, and documentation, and analyzed using Miles and Huberman's interactive model which included data reduction, data presentation, and conclusion drawn. The results of the study show that Metro TV has implemented several elements of the marketing communication mix, especially advertising, public relations, and digital marketing, but it has not been optimally integrated within the framework of Integrated Marketing Communication (IMC). The use of digital media, especially YouTube and TikTok, is the most effective strategy in reaching and increasing audience engagement. However, the brand awareness level of the Q&A program is still at the brand recognition stage, which indicates that the program has been recognized but has not yet reached the top of mind. . This study also found challenges in the form of changes in audience behavior, competition with digital content creators, and fluctuations in program performance. These findings indicate that increasing brand awareness does not only depend on digital media exposure, but also requires the integration of communication strategies, message consistency, and content innovation that matches the characteristics of digital audiences.